3D food printing of fresh vegetables using food hydrocolloids for dysphagic patients. (May 2021) - Pant, Aakanksha; Lee, Amelia Yilin; Karyappa, Rahul; Lee, Cheng Pau; An, Jia; Hashimoto, Michinao; Tan, U-Xuan; Wong, Gladys; Chua, Chee Kai; Zhang, Yi
Abstract: Three-dimensional food printing (3DFP) leads to advances in digital gastronomy by targeting consumers' specific requirements for nutrition customization and visual appeal. Dysphagia, or difficulty swallowing, is prevalent in elderly people and patients suffering from debilitating illnesses. Dysphagic diets require textural modifications to render them soft and safe to swallow. Diets must be visually pleasing to enable a greater food uptake to prevent malnutrition in patients. 3DFP so far has mainly utilized freeze-dried vegetable powders for shaping 3D designs. Our work focuses on fresh and frozen vegetables having better nutritional profile and low costs. Three different categories of vegetables are identified based on the number of hydrocolloids required to render them printable. Garden pea, carrot and bok choy are chosen as representatives in each category, which requires no HC, one type of HC and two types of HCs, respectively. Food inks are prepared by the addition of HCs i.e. xanthan gum (XG), kappa carrageenan (KC) and locust bean gum (LBG) for texture modification. Rheological, textural, microstructural and syneresis properties of the inks are examined. International dysphagia diet standardisation initiative (IDDSI) tests are done to assess the potential of the inks for dysphagic diets. Optimized ink formulations display excellent 3D printability, minimal water seepage, and dense microstructures with minimal amount of HCs. Using fresh vegetables instead of freeze-dried foods serves the purpose of preserving flavour and nutrition like real food. This in turn may bring 3DFP closer to the hospital and nursing home kitchens. Graphical abstract: Image 1 Highlights: Three-dimensional food printing of fresh vegetables for dysphagic patients. Three vegetable categories defined according to the number of hydrocolloids required to prepare food inks. Extensive characterization of food ink properties and its suitability for dysphagic patients. 3D-Printable food inks with no more than 2% hydrocolloids. A method of quantifying syneresis in food inks.